Assessing the impact of advertisement towards Malay consumers: an empirical study of fast food restaurants in Malaysia - Haque, A. K. M. Ahasanul; Rahman, Sabbir; Ahmed, Ismail Sayyed; Yasmin, Farzana; Asri, Almas (Society of Business and Management Dynamics, 2011)
The purpose of this paper is to explore consumers’ views on fast food restaurants advertisement. Data were collected by using convenient sampling method from Klang Valley area in Malaysia. The result of the research shows that customers’ are more influenced by internet advertisement followed by commercial advertising and print advertisement. The findings suggested some significant of implications which will help advertisers to create better fast food restaurant advertisements. For example, managers can change their slogans based on current situations which will help them to prepare on create suitable advertising for customers.